Emergence of HIV-1 CRF01AE/B unique recombinant forms in Kuala Lumpur, Malaysia - Tee, K.K.; Pon, C.K.; Kamarulzaman, A.; Ng, K.P. (2005)
Objectives: To investigate the molecular epidemiology of HIV-1 and to screen for the emergence of intersubtype recombinants in Kuala Lumpur, Malaysia. Design: A molecular epidemiology study was conducted among HIV-1 seropositive patients attending the University Malaya Medical Center (UMMC) from July 2003 to June 2004. Methods: Protease (PR) and reverse transcriptase (RT) gene sequences were derived from drug resistance genotyping assay of 100 newly diagnosed or antiretroviral-naive patients. These were phylogenetically analysed to determine the subtypes and recombination breakpoint analyses were performed on intersubtype recombinants to estimate the recombination breakpoint(s). Results: CRF01AE predominated in Kuala Lumpur with 65 in both PR and RT genes. B subtype was detected at 14 and 12 in PR and RT genes, respectively. C subtype was present at 1 in both genes. Overall, the concordance of PR and RT genes in discriminating subtypes/circulating recombinant forms (CRF) was high at 96. In this study, novel CRF01AE/B intersubtype recombinants were detected at high prevalence (22), including those isolates with subtype discordance. Thai variants of CRF01AE and B subtype were involved in the genesis of these unique recombinant forms (URF). Interestingly, 19 CRF01AE/B intersubtype recombinant isolates shared similar recombination breakpoints in both PR and RT genes. Several distinct URF were also identified. Conclusion: PR and RT genes can be utilized for subtype/CRF assessment with high degree of agreement, allowing concurrent surveillance of circulating HIV-1 subtypes with antiretroviral drug resistance genotyping tests. The emergence of highly identical CRF01AE/B intersubtype recombinants suggests the possibility of the appearance of a new circulating recombinant form in Kuala Lumpur. (c) 2005 Lippincott Williams C Wilkins.